A comparison between input modalities and languages in source-based multilingual argumentative writing - Arias-Hermoso, Roberto; Imaz Agirre, Ainara; Garro Larrañaga, Eneritz (Assessing writing, 2024)
This paper examines secondary education students’ multilingual writing based on two input modalities to understand the influence of input on argumentation and sourcing strategies. Participants produced texts in Basque, Spanish and English based on a video or a text, and texts were analysed to explore their production of argumentation elements and sourcing strategies. Differences were found between input modalities in the use of data and rebuttals, and in copying. Across-language differences were also found in the use of data and counterarguments, and in the use of original ideas and paraphrasing. Additionally, complex argumentation elements elicited more original ideas than simple ones. Findings suggest that different writing sub-processes might be activated when composing from different sources and that argumentation and sourcing might be transferable across languages. These results may have important implications for educators in multilingual programs who aim to support their students in acquiring academic writing skills in multiple languages. •Input modalities influenced students’ argumentation and source use strategies.•Across-language differences and similarities were found in source use strategies.•There is a relation between argumentation and source use.•Argumentation and sourcing skills might be transferred across languages.